European Economic Governance And Its Impact On The Collective Bargaining System: The Italian Case - M. Dolores Ferrara; Roberta Nunin (TRABAJO. Revista Iberoamericana de Relaciones Laborales, 2017)
The new economic governance has pursued a radical decentralisation of collective bargaining. The European system of economic policies represents a new model that can be described as new European interventionism and marks a paradigm change in the EU’s approach to collective bargaining to direct political intervention in national bargaining outcomes and procedures. The European economic governance pressure was very clearly on Italy, where the industrial relations system is strongly under pressure, since the “secret” letter sent from the ECB to Italy on August 5th, 2011, which immediately influenced both Italian legislator and social parties. This paper focuses on the trends of the Italian firm-level bargaining system from the perspective of the subjects who negotiate and the agreements’ effectiveness. In relation to the subjects, in Italy this pressure resulted in the adoption of the majority principle. From another point of view, in Italy, until the end of last century, the national-level collective agreement seemed to be ‘inviolable’, inserted as it was in a context of absolute centrality. If this was the traditional approach, in recent years the Italian system has experienced a shift away from the model, where the legal support has been combined with a ‘deconstruction’ of collective regulation. Here we will briefly consider these more recent dynamics, in particular by the intervention made by the Italian legislator with the so-called economic manoeuvre of August 2011 (Legislative Decree No. 138/2011, converted by Law No. 148/2011), which, in a framework of progressive fragmentation of labour relations, changed traditional attitudes.